2020
DOI: 10.3389/fspas.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Flare-Accelerated Electrons Quantified by Spatially Resolved Analysis

Abstract: Non-thermal electrons accelerated in solar flares produce electromagnetic emission in two distinct, highly complementary domains-hard X-rays (HXRs) and microwaves (MWs). This paper reports MW imaging spectroscopy observations from the Expanded Owens Valley Solar Array of an M1.2 flare that occurred on 2017 September 9, from which we deduce evolving coronal parameter maps. We analyze these data jointly with the complementary Reuven Ramaty High-Energy Solar Spectroscopic Imager HXR data to reveal the spatially-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
(69 reference statements)
2
13
0
Order By: Relevance
“…They showed that, because electrons of different energies resonate with the turbulence spectrum in different regimes (inertial range for high-energy electrons and dissipation range for low-energy electrons), an accelerated electron spectrum will develop naturally with hardening if the width of the flare termination shock is comparable to the electron's diffusion length scale. Subsequent observations, by e.g., Kong et al (2013) or most recently Kuroda et al (2020), support this mechanism. The work of Li et al (2013) illustrates that the ratio of the shock width to the diffusion length scale of accelerated particles is a key parameter when considering particle acceleration at a shock.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…They showed that, because electrons of different energies resonate with the turbulence spectrum in different regimes (inertial range for high-energy electrons and dissipation range for low-energy electrons), an accelerated electron spectrum will develop naturally with hardening if the width of the flare termination shock is comparable to the electron's diffusion length scale. Subsequent observations, by e.g., Kong et al (2013) or most recently Kuroda et al (2020), support this mechanism. The work of Li et al (2013) illustrates that the ratio of the shock width to the diffusion length scale of accelerated particles is a key parameter when considering particle acceleration at a shock.…”
Section: Introductionmentioning
confidence: 81%
“…We consider typical flare parameters as in Li et al (2013): a temperature of T∼5 MK, a magnetic field strength of B ∼ 200 G, and a proton number density of n ∼ 10 9 cm −3 . Using the Expanded Owens Valley Solar Array, Kuroda et al (2020) have examined an M1.2 flare that occurred on 2017 September 9. They found that the B field in that event was as high as 250 Gauss.…”
Section: A Pan-spectrum Fitting On the Hardening Spectrummentioning
confidence: 99%
“…The coronal magnetic field in flaring loops can be obtained from the analysis of microwave imaging spectroscopy data on the gyrosynchrotron emission associated with solar flares. The model spectral fitting of these data yields maps of the absolute value of the magnetic field and its direction relative to the LOS (Gary et al 2013;Fleishman et al 2020;Kuroda et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The latter is derived from the nonlinear force-free field (NLFFF) extrapolation of the coronal magnetic field reconstructed from photospheric magnetograms (Anfinogentov et al 2019), which Figure 1. Selected set of coronal magnetic field measurements using radio methods (Abramov-Maksimov & Gelfreikh 1983;Ryabov et al 1999;Brosius & White 2006;Bogod & Yasnov 2009Krucker et al 2010;Fleishman & Kuznetsov 2010;Anfinogentov et al 2019;Fleishman et al 2020;Kuroda et al 2020;Yu et al 2020) and the optical Zeeman method (Kuridze et al 2019). The meanings of the symbols are shown in the panel.…”
Section: Introductionmentioning
confidence: 99%
“…Nonthermal microwave emission, produced by a non-Maxwellian distribution of electrons gyrating in the coronal magnetic field, offers a unique view of the flux rope field lines rendered visible by the flare-accelerated nonthermal electrons (Narukage et al 2014;Wu et al 2016). When spectrally resolved imaging data are available with adequate bandwidth, spectral sampling, and temporal cadence, they can also be used to constrain the spatial distribution and temporal evolution of the magnetic field and nonthermal electrons (see, e.g., recent studies by Gary et al 2018;Chen et al 2020;Fleishman et al 2020;Kuroda et al 2020). However, such diagnostics for accelerated electrons and magnetic field of the flux ropes in the low corona have been illusive, mainly due to the lack of microwave imaging spectroscopy observations.…”
Section: Introductionmentioning
confidence: 99%